Two Brothers with Atypical UNC13D-Related Hemophagocytic Lymphohistiocytosis Characterized by Massive Lung and Brain Involvement - Giardino, Giuliana; De Luca, Maia; Cirillo, Emilia; Palma, Paolo; Romano, Roberta; Valeriani, Massimiliano; Papetti, Laura; Saunders, Carol; Cancrini, Caterina; Pignata, Claudio (Frontiers in Immunology, 2017)
Haemophagocytic lymphohistiocytosis is a potentially fatal hyperinflammatory condition. Variants in different genes have been associated with the familial forms of the syndrome (FHL), usually presenting within the first two years of life. Due to increasing awareness of the signs and symptoms of HLH and a better understanding of the genetic basis of the disease, FHL has been increasingly diagnosed in patients presenting beyond infancy. Here we report on two brothers with atypical, late onset HLH in which whole exome sequencing revealed a homozygous pathogenic UNC13D variant. In the first brother the clinical phenotype was dominated by a massive lung involvement. In the second brother a progressive neurological deterioration was observed. In both cases, the clinical manifestations at symptom onset were misleading, making the diagnosis difficult to achieve. This report expands the spectrum of clinical presentations of FLH3. Moreover, it highlights the importance to warn clinicians to keep a high level of suspicion in patients presenting with fever, cytopenia, splenomegaly of unknown origin and unresponsiveness to conventional treatment even beyond early childhood. Morevover, this report emphasizes that insidious neurologic symptoms may represent the initial or sole presenting sign of FHL, even in the absence of peripheral signs of activation.